Evaluation of sugar meal administered anti-Leishmania compounds on the vectorial capacity of the vector, Lutzomyia longipalpis - Tainá Neves Ferreira; Samara Graciane Costa Latgé; Tadeu Diniz Ramos; Felipe Cerqueira Demidoff; Edézio Ferreira Cunha-Júnior; Paulo Roberto Ribeiro Costa; Marcus Vinícius Nora de Souza; Cláudia Regina Brandão Gomes; Viv Maureen Dillon; Chaquip Daher Netto; Eduardo Caio Torres Santos; Rod James Dillon; et al. (PLoS ONE, 2025)
Multiple strategies involving the parasite-host-vector triad are necessary to control leishmaniasis. One option is to prevent or reduce transmission of the pathogen by the phlebotomine sand fly vectors. In this sense, it is essential to explore compounds that may influence the vectorial capacity of the insect and reduce its longevity. We investigated the effect of anti-Leishmania drugs administered via the sugar meal on longevity, blood feeding, oviposition, and parasite load on the third day of infection of the sand flies, to identify the most promising candidates for vector infection tests. We identified compounds that affected the longevity of sand flies (three pterocarpanquinones – LQB-475, LQB-181, and LQ-03; one hydroxyethylpiperazine, PMIC-4, and Pentamidine), reduced oviposition of females after blood feeding (LQB-181 and PMIC-4), but did not decrease infection rates or parasite loads. The results provide the effect of antiparasitic drugs from the perspective of the insect vector.